Design of Advertising Strategy Through Google Ads to Increase Export Sales of PT Kian Eka Cipta - Ahda Thahira Devatra (Riviera Publishing, 2024)
This era of globalization makes increasing the competitiveness of local products in the international market significant, especially for SME companies such as PT Kian Eka Cipta which is engaged in exporting furniture and handicrafts. Despite having high-quality products, the company faces challenges finding international buyers and marketing its products effectively. This research aims to design an advertising strategy through Google Ads to increase PT Kian Eka Cipta's export sales. The method used is descriptive qualitative with a case study approach. SWOT analysis and keyword analysis were applied to identify the company's strengths, weaknesses, opportunities, and threats and determine relevant keywords for advertising. The results showed that the potential market that can be developed through Google Ads is the United States. The strategy is focused on targeting specific audiences based on location, demographics, and interests. It is expected that the implementation of this strategy can increase PT Kian Eka Cipta's export sales by the predetermined targets.